Influence of volleyball and sports and health tourism on the physical, mental and social state of schoolchildren and students - Kateryna Mulyk; Aleksander Skaliy; Nurlan Mukazhanov; Andrzej Ostrowski; Volodymyr Paievskyi; Anatoliy Abdula (Kharkiv State Academy of Physical Culture, 2024)
Background and Study Aim. Based on research results, it has been established that various types of sports games and sports and health tourism are the most popular among schoolchildren and students. Various movements and actions in volleyball have great health benefits. They help strengthen the musculoskeletal system, improve overall metabolism, increase the activity of all organs and systems of all organisms and are a means of active recreation. In the conditions of hiking trip, a particularly important role is played by the high adaptive abilities of the body, based on the reactivity and lability of functional systems. The purpose of the study was to determine the influence of volleyball and sports and health tourism on the physical, mental and social health of schoolchildren and students. Material and Methods. The study involved 60 schoolchildren and 60 male students. Schoolchildren and students were divided into two groups (30 people in each group), who were engaged in volleyball and sports and health tourism sections. The study used methods to assess physical, mental and social health; level of satisfaction with quality of life; well-being, activity and mood. Results. The best indicators for physical health among schoolchildren and students were obtained in favor of those involved in sports and health tourism (p<0,05-0,01). The best level of mental and social health was found among students who spent a year studying in sports and health tourism sections (p<0,05-0,01), while schoolchildren, on the contrary, had the best results obtained from those who were involved in team sports. Conclusions. The results of the study indicate that playing sports games (volleyball and basketball) and sports and health tourism have a positive effect on the physical, mental and social health of schoolchildren and students. These studies indicate that school-age children are characterized by team sports, which are more emotional and serve as an effective means of physical education for this age category. Students are more interested in organizing classes in sports and health tourism, which include participation in competitions in various types of tourism and weekend trips held in the fresh air. Thus, it can be stated that the influence of sports games and sports and health tourism on the psychological sphere of schoolchildren and students contributes to positive changes in their psyche, creates a persistent, cheerful, active state, generating positive emotions and ensures increased satisfaction with life in general, which in turn affects the health of children and youth.